2021
DOI: 10.1007/s10198-021-01300-5
|View full text |Cite
|
Sign up to set email alerts
|

Different levels of care for follow-up of adults with congenital heart disease: a cost analysis scrutinizing the impact on medical costs, hospitalizations, and emergency department visits

Abstract: Baudouin Foundation (Fund Joseph Oscar Waldmann-Berteau & Fund Walckiers Van Dessel).JDB is supported as senior clinical researcher, EG as postdoctoral researcher, and LVB as predoctoral researcher by the Research Foundation Flanders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Ongoing regular care with a congenital cardiologist reduces death 2 , 38 and improves outcomes across the CHD anatomic severity levels. 41 Individuals may be out of routine congenital cardiology care for a variety of socioeconomic reasons, including limited access to transportation to centralized tertiary care centers, lack of insurance access, language barriers, lack of paid sick leave, inability to take time off work, economic constraints, and limited understanding of the purpose and benefits of routine surveillance care for their CHD. 5 Thus, individuals who are out of specialty care may seek care through the ED at a higher rate and in a sicker state than those individuals who have remained in congenital cardiology care.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing regular care with a congenital cardiologist reduces death 2 , 38 and improves outcomes across the CHD anatomic severity levels. 41 Individuals may be out of routine congenital cardiology care for a variety of socioeconomic reasons, including limited access to transportation to centralized tertiary care centers, lack of insurance access, language barriers, lack of paid sick leave, inability to take time off work, economic constraints, and limited understanding of the purpose and benefits of routine surveillance care for their CHD. 5 Thus, individuals who are out of specialty care may seek care through the ED at a higher rate and in a sicker state than those individuals who have remained in congenital cardiology care.…”
Section: Discussionmentioning
confidence: 99%
“…[ 51 ] assessed healthcare utilisation of ACHD patients in Israel and demonstrated that this population had higher rates of healthcare utilisation than the general population, with those on geographic peripheries being associated with fewer specialist attendances. Linkage with administrative data has also shown that specialised CHD care is associated with lower medical costs and better economic outcomes for patients [ 52 ]. Inclusion of insights drawn from linked administrative data in a clinic planning tool such as the one presented here would allow ACHD services to be delivered with a greater level of precision.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Ongoing regular care with a congenital cardiologist reduces mortality 2,38 and improves outcomes across the CHD anatomic severity levels. 41 Individuals may be out of routine congenital cardiology care for a variety of socioeconomic reasons, including limited access to transportation to centralized tertiary care centers, lack of insurance access, language barriers, lack of paid sick leave, inability to take time off work, economic constraints and limited understanding of the purpose and benefits of routine surveillance care for their CHD. 5 Thus, individuals who are out of specialty care may seek care through the ED at a higher rate and in a sicker state than those individuals who have remained in congenital cardiology care.…”
Section: Discussionmentioning
confidence: 99%